THE FOUNDATIONS OF INTERNATIONAL JUS COGENS - Cerveira Cittadino, Rodrigo (2018)
The article focuses on the justificatory theories about international jus cogens, specifically the most known: the naturalist theory, the legal posivist theory, the international public order theory and other theories with a sociological aspect.  We do not intend to propose a solution to the biggest problem of what would be the exact contours of jus cogens or its nomogenetic process – that is, the question of why would an ordinary norm of International Law achieve (or why would it deserve to achieve) the quality of a peremptory norm. We content ourselves with exposing the limits of each one of these foundations, with emphasis on the legal positivist theory. The proposal we try to advance is that these different perspectives would have much to gain if they communicated with each other.